Permeability in Malaysian hot mix asphalt mixtures - Muhamad Nor, Nur Syahriza (2006)
Many studies have shown that the air void content affect the permeability of the hot mix asphalt (HMA) mixtures. This study aims to evaluate the characteristic of local HMA mixtures and find a relationship between air void and permeability, and then obtain in-situ minimum density level in order to produce impermeable pavements. Eight types of HMA mixes were produced; ACW14, ACW20, BMW14, BMW20, ACB28, BMB28, BMR28 and BML10. Ten samples for each mix with different compactive efforts; 75, 60, 50, 40 and 30 were prepared. The permeability test was conducted to get the coefficient of permeability. From the test conducted the permeability versus air void content graphs were plotted. The relationship between permeability and air void content is directly related. As the air void content increased the permeability also increased. Therefore, it is suggested that the maximum in-place air void contents for wearing course, ACW14 and ACW20 are 6.4 and 4.2% or 98 and 100% of Marshall density design at 4% air void respectively while the air void contents for wearing course, BMW14 and BMW20 are 5.4 and 6.0% or 99 and 98% of Marshall density. For binder course, ACB28 and BMB28, 6.4 and 6.1% air void contents or 98% of Marshall density are recommended. For levelling, BML10 and bituminous roadbase, BMR28 course, 12.9 and 7.2% air void content or 91 and 97% of Marshall density are proposed respectively